Safety and long-term immunological effects of CryJ2-LAMP plasmid vaccine in Japanese red cedar atopic subjects: A phase I study. Issue 12 (2nd December 2017) - Su, Yan; Romeu-Bonilla, Eliezer; Anagnostou, Athanasia; Fitz-Patrick, David; Hearl, William; Heiland, Teri
ABSTRACT: Japanese Red Cedar (JRC) pollen induced allergy affects one third of Japanese and the development of effective therapies remains an unachieved challenge. We designed a DNA vaccine encoding CryJ2 allergen from the JRC pollen and Lysosomal Associated Membrane Protein 1 (LAMP-1) to treat JRC allergy. These Phase IA and IB trials assessed safety and immunological effects of the investigational CryJ2-LAMP DNA vaccine in both non-sensitive and sensitive Japanese expatriates living in Honolulu, Hawaii. In the Phase IA trial, 6 JRC non-sensitive subjects and 9 JRC and/or Mountain Cedar (MC) sensitive subjects were given 4 vaccine doses (each 4mg/1ml) intramuscularly (IM) at 14-day intervals. Nine JRC and/or MC sensitive subjects were given 4 doses (2 mg/0.5 ml) IM at 14-day intervals. The safety and functional biomarkers were followed for 132 d. Following this, 17 of 24 subjects were recruited into the IB trial and received one booster dose (2 mg/0.5 ml) IM approximately 300 d after the first vaccination dose to which they were randomized in the first phase of the trial. All safety endpoints were met and all subjects tolerated CryJ2-LAMP vaccinations well. At the end of the IA trial, 10 out of 12 JRC sensitive and 6 out of 11 MC sensitive subjects experienced skin test negative conversion, possibly related to the CryJ2-LAMP vaccinations. Collectively, these data suggested that the CryJ2-LAMP DNA vaccine is safe and may be immunologically effective in treating JRC induced allergy.